Peran Komunikasi Publik Melalui Media Sosial Instagram dalam Meningkatkan Keterbukaan Informasi Publik di BKN RI - Maulani, Ridho Zinta; Syarah, Maya May; Susilowati, Susilowati (Brand Communication, 2024)
Public communication through social media is essential for facilitating the dissemination of public information and increasing public engagement. This research examines how public communication via Instagram enhances public information transparency at the National Civil Service Agency (BKN). The study employs a descriptive qualitative method with a descriptive case study approach. Data were collected through structured interviews, observations, and content analysis related to public communication activities on the Instagram account @bkngoidofficial. The findings indicate that public communication via Instagram significantly improves transparency and accessibility of public information to the community. Active interactions between BKN and the public through comments and direct messages also enhance public trust in the information provided. In conclusion, the use of public communication through Instagram is deemed effective in supporting information transparency at BKN. Additionally, regular evaluations of the effectiveness of public communication via Instagram are crucial to ensure the sustainability and improvement of the quality of information delivered.